Brainstem BDNF neurons are downstream of GFRAL/GLP1R signalling - Claire H. Feetham; Valeria Collabolletta; Amy A. Worth; Rosemary Shoop; Sam Groom; Court Harding; Mehdi Boutagouga Boudjadja; Tamer Coskun; Paul J. Emmerson; Giuseppe D’Agostino; Simon M. Luckman (Nature Communications)
Abstract Growth differentiation factor 15, GDF15, and glucagon-like peptide-1 (GLP-1) analogues act through brainstem neurons that co-localise their receptors, GDNF-family receptor α-like (GFRAL) and GLP1R, to reduce food intake and body weight. However, their use as clinical treatments is partially hampered since both can also induce sickness-like behaviours, including aversion, that are mediated through a well-characterised pathway via the exterolateral parabrachial nucleus. Here, in mice, we describe a separate pathway downstream of GFRAL/GLP1R neurons that involves a distinct population of brain-derived neurotrophic factor (BDNF) cells in the medial nucleus of the tractus solitarius. Thus, BDNFmNTS neurons are required for the weight-reducing actions of both GDF15 and the GLP1RA, Exendin-4. Moreover, acute activation of BDNFmNTS neurons is sufficient to reduce food intake and drive fatty acid oxidation and might provide a route for longer-term weight loss.